A useful protocol for in situ RT-PCR on plant tissues - Urbanczyk-Wochniak, E.; Filipecki, M.; Przybecki, Z.
This study describes an effective method of in situ RT-PCR (RT-ISPCR)that was developed to localize gene expression in plant tissues. This RT-PCR technique was performed on sectioned tissues of female buds of the cucumber GY3 inbred line. The CUS1 gene, encoding the MADS-box type (agamus-like)protein, the expression pattern of which was described earlier [10], was used as a marker gene for optimisation of steps in the in situ RT-PCR inside the cells.For the identificat ion of RT-PCR products inside the cells of the female buds, they were fixed in FAA solution, embedded in Paraplast Plus and cut into7mm thick sections which were dewaxed by immersion in HistoClear and dehydrated with ethanol. They were washed in water, th en in 0.02M HCl, 2xSSC and PBS buffer. In the next step of tissue pretreatment, the sections were digested with
Keywords: IN SITU RT-PCR; GENE EXPRESSION; PARAFFIN SECTIONS; CUCUMIS SATIVUS L